Extracellular Reactive Oxygen Species (ROS) Production in Fresh Donkey Sperm Exposed to Reductive Stress, Oxidative Stress and NETosis - Iván Yánez-Ortiz; Jaime Catalán; Yentel Mateo-Otero; Marta Dordas-Perpinyà; Sabrina Gacem; Natalia Yeste; Anna Bassols; Marc Yeste; Jordi Miró (MDPI AG, 2021)
Jenny shows a large endometrial reaction after semen influx to the uterus with a large amount of polymorphonuclear neutrophils (PMN) migrating into the uterine lumen. PMN act as a sperm selection mechanism through phagocytosis and NETosis (DNA extrudes and, together with proteins, trap spermatozoa). While a reduced percentage of spermatozoa are phagocytosed by PMN, most are found to be attached to neutrophil extracellular traps (NETs). This selection process together with sperm metabolism produces a large amount of reactive oxygen species (ROS) that influence the reproductive success. The present study aimed to determine the extracellular ROS production in both sperm and PMN. With this purpose, (1) donkey sperm were exposed to reductive and oxidative stresses, through adding different concentrations of reduced glutathione (GSH) and hydrogen peroxide (H2O2), respectively; and (2) PMN were subjected to NETosis in the presence of the whole semen, sperm, seminal plasma (SP) or other activators such as formyl-methionyl-leucyl-phenylalanine (FMLP). Extracellular ROS production (measured as H2O2 levels) was determined with the Amplex® Red Hydrogen Peroxide/Peroxidase Assay Kit. Donkey sperm showed more resilience to oxidative stress than to the reductive one, and GSH treatments led to greater H2O2 extracellular production. Moreover, not only did SP appear to be the main inducer of NETosis in PMN, but it was also able to maintain the extracellular H2O2 levels produced by sperm and NETosis.